2014
DOI: 10.1002/asia.201402883
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Platinum Nanoflowers on Polydopamine‐Coated Reduced Graphene Oxide for Methanol Oxidation and Oxygen Reduction Reactions

Abstract: The morphology- and size-controlled synthesis of branched Pt nanostructures on graphene is highly favorable for enhancing the electrocatalytic activity and stability of Pt. Herein, a facile approach is developed for the efficient synthesis of well-dispersed Pt nanoflowers (PtNFs) on the surface of polydopamine (PDA)-modified reduced graphene oxide (PDRGO), denoted as PtNFs/PDRGO, in high yield. The synthesis was performed by a simple heating treatment of an aqueous solution that contained K2PtCl4 and PDA-modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…As such, PANI serves as a cross-linker between metal NPs and carbon support by forming strong metal-N bonds. [150][151][152] Ionic-liquid polymers, 153 PDA, [154][155][156] Ppy, 157 polybenzimidazole (PBI), 78,[158][159][160][161] PVP, 162 and polyethyleneimine (PEI) 163 have broadened the application of polymers for the surface modification of carbon support materials as well. Intriguingly, it is reported that PDA serves not only as a crosslinking agent, but also as a reductant for the in situ reduction and nucleation of metal species without the need of adding any other reducing agents during the synthesis of polymer-modified carbon-supported metal NPs.…”
Section: Modification Of the Carbon Support By Surface Overcoatingmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, PANI serves as a cross-linker between metal NPs and carbon support by forming strong metal-N bonds. [150][151][152] Ionic-liquid polymers, 153 PDA, [154][155][156] Ppy, 157 polybenzimidazole (PBI), 78,[158][159][160][161] PVP, 162 and polyethyleneimine (PEI) 163 have broadened the application of polymers for the surface modification of carbon support materials as well. Intriguingly, it is reported that PDA serves not only as a crosslinking agent, but also as a reductant for the in situ reduction and nucleation of metal species without the need of adding any other reducing agents during the synthesis of polymer-modified carbon-supported metal NPs.…”
Section: Modification Of the Carbon Support By Surface Overcoatingmentioning
confidence: 99%
“…Intriguingly, it is reported that PDA serves not only as a crosslinking agent, but also as a reductant for the in situ reduction and nucleation of metal species without the need of adding any other reducing agents during the synthesis of polymer-modified carbon-supported metal NPs. 155,164,165 In addition to oxidative polymerization, an easy-handling process involving a simple mixing of the carbon support with an organic entity containing solution followed by a thorough rinsing step has been applied for overcoating with PyPBI, PBI and PVP. 78,[159][160][161][162][166][167][168] Moreover, by utilizing the amide reaction between the -COOH groups of carbon black and the -NH 2 groups of amine-terminated poly(N-isopropylacrylamide) (PNIPAM), Jung et al 169 demonstrated the covalent functionalization of the carbon support with polymers for efficient anchoring of metal species.…”
Section: Modification Of the Carbon Support By Surface Overcoatingmentioning
confidence: 99%
“…This is because the oxygen-functional groups in the interlayer spacing was gradually removed in the process of GO reduction. 45,46 Fourier transform infrared (FTIR) spectroscopy was used to reveal the functional groups contained in the as-prepared materials. As shown in Fig.…”
Section: Morphology and Structure Of G-pda-m Materialsmentioning
confidence: 99%
“…[16][17] In previous literatures, surfactants are crucial in the formation of the self-assembled nanostructures. [18][19] It is generally believed that the building blocks for oriented aggregation/attachment are usually nanoparticles with surfaces stabilized by an organic coating, and weakly protected nanoparticles often undergo entropy-driven random aggregation. 20 However, excessive surfactants are difficult to be removed from as-obtained nanoassemblies and responsible for the dramatic reduction of properties.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Recently, Pt nanostructures self-assembled from small Pt nanocrystals have become an area of considerable interest due to their many unique structural characteristics, such as high porosity, large surface area per unit volume, interconnected open-pore structures and stable selfassembled frameworks. [11][12][13] Consequently, many efforts devoted to this area have led to the fabrication of hollow Pt spheres with nano-channels, 14 three-dimensional dendritic Pt, 15 Pt fibrils via self-assembly of peptides, 13 and so on. But to date, the morphology control of Pt nanoassemblies has been limited to be achieved without the use of a template.…”
Section: Introductionmentioning
confidence: 99%